Monitoring the Sphingolipid de novo Synthesis by Stable-Isotope Labeling and Liquid Chromatography-Mass Spectrometry - Wigger, Dominik; Gulbins, Erich; Kleuser, Burkhard; Schumacher, Fabian (Frontiers in Cell and Developmental Biology, 2019)
Sphingolipids are a class of lipids that share a sphingoid base backbone. They exert various effects in eukaryotes, ranging from structural roles in plasma membranes to cellular signaling. De novo sphingolipid synthesis takes place in the endoplasmic reticulum (ER), where the condensation of the activated C16 fatty acid palmitoyl-CoA and the amino acid L-serine is catalyzed by serine palmitoyltransferase (SPT). The product, 3-ketosphinganine, is then converted into more complex sphingolipids by additional ER-bound enzymes, resulting in the formation of ceramides. Since sphingolipid homeostasis is crucial to numerous cellular functions, improved assessment of sphingolipid metabolism will be key to better understanding several human diseases. To date, no assay exists capable of monitoring de novo synthesis sphingolipid in its entirety. Here, we have established a cell-free assay utilizing rat liver microsomes containing all the enzymes necessary for bottom-up synthesis of ceramides. Following lipid extraction, we were able to track the different intermediates of the sphingolipid metabolism pathway, namely 3-ketosphinganine, sphinganine, dihydroceramide, and ceramide. This was achieved by chromatographic separation of sphingolipid metabolites followed by detection of their accurate mass and characteristic fragmentations through high-resolution mass spectrometry and tandem-mass spectrometry. We were able to distinguish, unequivocally, between de novo synthesized sphingolipids and intrinsic species, inevitably present in the microsome preparations, through the addition of stable isotope-labeled palmitate-d3 and L-serine-d3. To the best of our knowledge, this is the first demonstration of a method monitoring the entirety of ER-associated sphingolipid biosynthesis. Proof-of-concept data was provided by modulating the levels of supplied cofactors (e.g., NADPH) or the addition of specific enzyme inhibitors (e.g., fumonisin B1). The presented microsomal assay may serve as a useful tool for monitoring alterations in sphingolipid de novo synthesis in cells or tissues. Additionally, our methodology may be used for metabolism studies of atypical substrates – naturally occurring or chemically tailored – as well as novel inhibitors of enzymes involved in sphingolipid de novo synthesis.